Jawabanmu

2014-03-25T22:50:58+07:00
F(x) = x² -2x +3
f⁻¹(x) = ?

f(x)= y
x²- 2x + 3 = y
 x      =   y- x² - 3
             -------------
                  -2
    x    = -x²+y-3         - ( -x²+y - 3)          x²-y+3
            ------------  = ----------------------  =  -------------
                -2                  - (-2)                   2

                  x²-x+3
jadi f⁻¹(x) =  ----------
                      2



semoga bermanfaat y 
mav y kalo salah :)
2014-03-25T22:53:56+07:00
f(x) =  x^{2} - 2x +3 

f ^{-1} = ...?

y =  x^{2} - 2x + 3
y  - 2 = x² - 2x + 3 -2 
y - 2 = x² - 2x + 1
y - 2 =  (x - 1)^{2}

 \sqrt{y - 2} = x - 1

 \sqrt{y - 2}  + 1=x

f^{-1}(x) =  \sqrt{x - 2} + 1
1 5 1